Utilization Focused Evaluation at Bahria University Medical & Dental College - Rehman, Rehana; Ali, Rabiya; Moazzam, Hina; Shaikh, Saifullah (Pakistan journal of medical sciences, 2017)
To evaluate integrated learning program of neurosciences for continuation of integrated learning in the forthcoming teaching and learning modules of undergraduate medical curriculum at Bahria University Medical & Dental College (BUMDC). A mixed method design was conducted from August 2016to February2017 after ethical approval from BUMDC. The quantitative aspect was evaluated retrospectively by desk records ofmarks obtained in integrated module and nonintegrated module. Focused group discussionwere conducted with primary intended users (chair of integration committee, faculty and students of first and second year MBBS)to share their expectations and concerns and get responses on key evaluation questions for implementationand outcome evaluation of integrated learning program. The desk record revealed a positive perception of students and faculty at the time of implementation with improvement in results after integration in subjects of basic sciences. The discussions highlighted reasons which resulted in failure of its continuation and affirmedreadiness for re-induction and continuation of integration with clinicalsciences. Evaluators considered approval and re-application of integrated curriculum at BUMDC after utilization focused evaluation.